Disrupted posterior cingulate–amygdala connectivity in postpartum depressed women as measured with resting BOLD fMRI - Chase, Henry W. (Oxford University Press, 2014)
Disengagement of emotion regulation circuits was previously shown in depressed mothers and was hypothesized to underlie the impaired maternal–infant sensitivity described in postpartum depression (PPD). We hypothesized similarly reduced resting-state functional connectivity in default mode network (DMN) regions involved in social cognition in PPD. Resting-state functional MRI, clinical and mother–infant attachment data were obtained from 14 unmedicated postpartum women with major depression and 23 healthy postpartum women. Posterior cingulate cortex (PCC) time series were extracted, filtered between 0.007 and 0.08 Hz and used as regressors in a whole brain general linear model analysis. PCC–right amygdala connectivity was significantly disrupted in depressed compared to healthy mothers for low-frequency neural activity, showing a negative (inverse) coupling in the depressed group but not in the controls. PCC–right amygdala connectivity was positively correlated with PCC–parahippocampus connectivity. Resting connectivity patterns of positive co-activations in postpartum women mirrored the canonical DMN. These findings of reduced PCC–amygdala coupling raise the possibility that PPD might involve the disruption of outward, preventative aspects of self-relevant thought and theory of mind/empathy processes. Further integrated studies of neural connectivity and these cognitive/behavioral dimensions are warranted.